Increased CD34 in pancreatic islet negatively predict islet β-cell decrease in type1 diabetes model - Huang, Shichen; Li, Zhiyuan; Sun, Yuhan; Chen, Baiyi; Jiang, Yuxin; Hong, Feng (Frontiers in Physiology, 2022)
Islet β-cell biomarkers can reflect changes in the number and function of islet β-cells in the prediabetes or early diabetes stage. CD34 is a commonly used stem cell biomarker; however, its expression and function in pancreatic islets remain unclear. In the present study, double immunofluorescence staining, proteomic bioinformatics analysis, and correlation analysis were used to explore the potential of CD34 as an islet β-cell biomarker. Bioinformatics analysis revealed that the amino acid sequence of CD34 was conserved among multiple species and abundantly expressed on mouse and human pancreatic tissues. Immunofluorescence demonstrated that in the control rat pancreas, CD34 was expressed on glucagon-labeled islet α-cells but not on insulin-labeled islet β-cells. Furthermore, the proportion of CD34-positive cells, which were also positive for glucagon, was significantly increased in alloxan-induced diabetes models. Statistical analysis revealed that the expression of CD34 was negatively correlated with the number of insulin-labeled islet β-cells during diabetes progression in dose-dependent fashion in alloxan-induced diabetes models. Furthermore, the results suggested that the transdifferentiation of islet β-cells into islet α-cells may occur in the process of diabetes. Thus, the present study demonstrated that CD34 is expressed on islet α-cells, and its number is linearly and negatively correlated with the number of islet β-cells, suggesting that CD34 can be used as a prospective biomarker for islet β-cells in the early diagnosis of diabetes. The study also suggests the transformation of β-cells to α-cells in diabetes which provide a potential to be applied towards diabetes mechanism research.